2021
DOI: 10.1111/ffe.13605
|View full text |Cite
|
Sign up to set email alerts
|

Creep damage behaviors of red sandstone subjected to uniaxial compression after high‐temperature heat treatment using acoustic emission technology

Abstract: This work discusses the results from tests conducted to investigate the uniaxial compression and creep behavior of red sandstone. An original untreated sample and an 800°C treated sample were selected to carry out the experiments. High temperature had an obvious influence on the mechanical properties of the red sandstone. The relationship between creep strain and instantaneous strain, as well as the instantaneous deformation modulus and creep viscosity coefficient, was analyzed. High temperature reduced the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…A detailed understanding of the compressive behavior of granite under environments of high temperature and water is critical for deep underground exploration and engineering, especially the understanding of granite, a deep hard bedrock faced commonly in the underground engineering. It is considered as the target formation for deep geothermal energy projects and host rock for nuclear waste disposals 1,2 . The understanding, on the one hand, is beneficial for optimizing the design to improve the efficiency of drilling technologies, such as hydraulic fracturing, thermal spallation drilling, or blasting 11,12 for exploring geothermal energy; on the other hand, it has great significance for designing structures within the rock of nuclear waste disposals projects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed understanding of the compressive behavior of granite under environments of high temperature and water is critical for deep underground exploration and engineering, especially the understanding of granite, a deep hard bedrock faced commonly in the underground engineering. It is considered as the target formation for deep geothermal energy projects and host rock for nuclear waste disposals 1,2 . The understanding, on the one hand, is beneficial for optimizing the design to improve the efficiency of drilling technologies, such as hydraulic fracturing, thermal spallation drilling, or blasting 11,12 for exploring geothermal energy; on the other hand, it has great significance for designing structures within the rock of nuclear waste disposals projects.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing energy demand, exploring resources at a significant depth to access geothermal, 1,2 underground coal gasification, [3][4][5] and minerals, as well as storing nuclear waste deep underground, attracts increasing attention. 1,[5][6][7][8] The deep underground has some completely different environmental characteristics, compared with shallow layers, for example, the high temperature rising by 0.3-0.4 C/km 9 and the widely distributed groundwater.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, previous studies have found that the creep characteristics of sandstone is affected by many external factors, such as confining pressure, [7][8][9] temperature, [10][11][12] water content, [13][14][15] and pore pressure. [16][17][18] Pan et al 19 investigated the influence of high temperature on the creep damage behaviors of red sandstone. They found that temperature has an obvious influence on uniaxial compressive strength, Young's modulus, and failure modes of red sandstone.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the safety of underground filling mining areas, a lot of research on the mechanical properties, loss and failure characteristics of rock and backfill have been carried out world widely [4][5][6][7]. In terms of rock damage and failure, many scholars have analyzed the damage evolution in the process of rock deformation, and failure through experimental means and established constitutive models [8][9][10][11]. Bustamante et al [12] proposed a nonlinear constitutive relation to simulate the properties of sandstone and studied the compressional and shear wave properties of rock under compression, finding that the compressional wave velocity is related to the compressive load.…”
Section: Introductionmentioning
confidence: 99%